2005
DOI: 10.1002/ajim.20178
|View full text |Cite
|
Sign up to set email alerts
|

Potential occupational risks for neurodegenerative diseases

Abstract: Support was observed for hypothesized excess neurodegenerative disease associated with a variety of occupations, 60 Hz magnetic fields and welding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
6
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(206 citation statements)
references
References 86 publications
8
189
6
3
Order By: Relevance
“…OCCUPATIONAL EXPOSURES AND SYSTEMIC AUTOIMMUNE DISEASES (36)(37)(38). Because the job titles used for our analyses were defined as the decedents' "usual" rather than most recent occupations, we intended to capture occupational exposures that occurred prior to the onset of disease.…”
Section: Discussionmentioning
confidence: 99%
“…OCCUPATIONAL EXPOSURES AND SYSTEMIC AUTOIMMUNE DISEASES (36)(37)(38). Because the job titles used for our analyses were defined as the decedents' "usual" rather than most recent occupations, we intended to capture occupational exposures that occurred prior to the onset of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Also, epidemiological data on populations occupationaly exposed to ELF fields have been interpreted as indicative of increased incidence of those cancers and other malignancies [see reviews by Ahlbom et al (3), Park et al (4) and Kheifets et al (5)]. On the basis of the epidemiological evidence, particularly on leukemia, the International Agency for Research on Cancer (IARC) has classified weak ELF MF as a 'possible carcinogenic' agent (class 2B).…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study, to our knowledge, to investigate the risk for Parkinson's disease among gardeners. Several studies have found positive associations between farming and Parkinson's disease (12)(13)(14)(15)(16), including a Danish study, in which men working in agriculture and horticulture had a significantly higher risk for a first hospital admission for Parkinson's disease (SHR 132, 95% CI 111-156) than the general Danish population (17). It has been suggested that the increased risks of farmers Kenborg et al and agricultural workers are related to exposure to pesticide (17,18), and this hypothesis has been examined in several recent epidemiological studies, most of which found positive associations (18-27), while few were unable to find such effects (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%